The anatomical basis for transcutaneous auricular vagus nerve stimulation - Butt, Mohsin F. (J Anat, 2019)
The array of end organ innervations of the vagus nerve, coupled with increased basic science evidence, has led to vagus nerve stimulation (VNS) being explored as a management option in a number of clinical disorders, such as heart failure, migraine and inflammatory bowel disease. Both invasive (surgically implanted) and non‐invasive (transcutaneous) techniques of VNS exist. Transcutaneous VNS (tVNS) delivery systems rely on the cutaneous distribution of vagal afferents, either at the external ear (auricular branch of the vagus nerve) or at the neck (cervical branch of the vagus nerve), thus obviating the need for surgical implantation of a VNS delivery device and facilitating further investigations across a wide range of uses. The concept of electrically stimulating the auricular branch of the vagus nerve (ABVN), which provides somatosensory innervation to several aspects of the external ear, is relatively more recent compared with cervical VNS; thus, there is a relative paucity of literature surrounding its operation and functionality. Despite the increasing body of research exploring the therapeutic uses of auricular transcutaneous VNS (tVNS), a comprehensive review of the cutaneous, intracranial and central distribution of ABVN fibres has not been conducted to date. A review of the literature exploring the neuroanatomical basis of this neuromodulatory therapy is therefore timely. Our review article explores the neuroanatomy of the ABVN with reference to (1) clinical surveys examining Arnold’s reflex, (2) cadaveric studies, (3) fMRI studies, (4) electrophysiological studies, (5) acupuncture studies, (6) retrograde tracing studies and (7) studies measuring changes in autonomic (cardiovascular) parameters in response to auricular tVNS. We also provide an overview of the fibre composition of the ABVN and the effects of auricular tVNS on the central nervous system. Cadaveric studies, of which a limited number exist in the literature, would be the ‘gold‐standard’ approach to studying the cutaneous map of the ABVN; thus, there is a need for more such studies to be conducted. Functional magnetic resonance imaging (fMRI) represents a useful surrogate modality for discerning the auricular sites most likely innervated by the ABVN and the most promising locations for auricular tVNS. However, given the heterogeneity in the results of such investigations and the various limitations of using fMRI, the current literature lacks a clear consensus on the auricular sites that are most densely innervated by the ABVN and whether the brain regions secondarily activated by electrical auricular tVNS depend on specific parameters. At present, it is reasonable to surmise that the concha and inner tragus are suitable locations for vagal modulation. Given the therapeutic potential of auricular tVNS, there remains a need for the cutaneous map of the ABVN to be further refined and the effects of various stimulation parameters and stimulation sites to be determined.